Reliability and Statistics in Transportation and Communication Selected Papers from the 17th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'17, 18-21 October, 2017, Riga, Latvia (Lecture Notes in Networks and Systems,, 2018)
This book reports on cutting-edge theories and methods for analyzing complex systems, such as transportation and communication networks and discusses multi-disciplinary approaches to dependability problems encountered when dealing with complex systems in practice. The book presents the most noteworthy methods and results discussed at the International Conference on Reliability and Statistics in Transportation and Communication (RelStat), which took place in Riga, Latvia on October 18 - 21, 2017. It spans a broad spectrum of topics, from mathematical models and design methodologies, to software engineering and data security issues, as well as practical problems in technical systems, such as transportation, and telecommunications.